Huntington’s Disease Patient-Derived Astrocytes Display Electrophysiological Impairments and Reduced Neuronal Support - Garcia, Veronica J.; Rushton, David J.; Tom, Colton M.; Allen, Nicholas D.; Kemp, Paul J.; Svendsen, Clive N.; Mattis, Virginia B. (Frontiers in Neuroscience, 2019)
In Huntington’s disease (HD), while the ubiquitously expressed mutant Huntingtin (mtHTT) protein primarily compromises striatal and cortical neurons, glia also undergo disease-contributing alterations. Existing HD models using human induced pluripotent stem cells (iPSCs) have not extensively characterized the role of mtHTT in patient-derived astrocytes. Here physiologically mature astrocytes are generated from HD patient iPSCs. These human astrocytes exhibit hallmark HD phenotypes that occur in mouse models, including impaired inwards rectifying K+ currents, lengthened spontaneous Ca2+ waves and reduced cell membrane capacitance. HD astrocytes in co-culture provided reduced support for the maturation of iPSC-derived neurons. In addition, neurons exposed to chronic glutamate stimulation are not protected by HD astrocytes. This iPSC-based HD model demonstrates the critical effects of mtHTT on human astrocytes, which not only broadens the understanding of disease susceptibility beyond cortical and striatal neurons but also increases potential drug targets.